(untitled) (Journal of the Bangladesh Agricultural University, 2019)
The experiment was conducted to find out the effects of hydropriming on seed germination, seedling growth and yield of bitter. Two single factor experiments were conduced at the laboratory and field of Seed Science and Technology Department following completely randomized design with three replications and randomized complete block design with five replications, rspectively. The experiments comprised six soaking treatments viz. T0: untreated (control), T1: tap water (around 25º ± 2º C) for overnight, T2:cold water (12ºC) for 5 min, T3: cold water (12ºC) for 10min, T4:cold water (12ºC) for 15min, T5: hot water (45ºC) for 5 min and T6: hot water (45ºC) for 10min soaking. The highest germination (88.0%) was obtained from T5 treatment and the lowest germination (30.0%) was recorded in control treatment. It was also observed that T5 treatment exehibited superior performances in respect of most of the parameters studied in the laboratory as well as in fiield experiment as compeared to control treatment. In respect of fruit yield per plant, maximum number of fruits obtained from T5 treatment (16 fruits/plant) followed by T6 (14 fruit/plant), T1 (12 fruit/plant), T2 (12.0 fruit/plant), T3 (11.2 fruit/plant) and T4 (11.2 fruit/plant) and the minimum number of fruits per plant recorded from the control treatment (7.6). From the findings of these study it can be concluded that bitter gourd seeds soaked in hot water at 45ºC for 5 min could improve seed germination, expedite seedling growth and eventually increase the yield of fruit. J Bangladesh Agril Univ 17(3): 281–287, 2019